Flexible majority rules - Erlenmaier, Ulrich; Gersbach, Hans (CESifo working papers, 2001)
In this paper we introduce flexible majority decision rules where the size of the majority depends on the proposal made by the agenda setter. Flexible majority rules can mitigate the disadvantages of democracies in the provision of public projects. In many cases, the combination of the principles taxation constraint to majority winners, a ban on subsidies, costly agenda setting and flexible majority rules constitute a socially optimal democratic constitution. Flexible majority rules might also be a useful decision-making procedure in other circumstances.